Prinsip-prinsip Pengawasan dalam Al-Qur'an dan Hadits: Implikasi terhadap Etika dan Kepemimpinan dalam Masyarakat Muslim - Mistam, Mistam; Maujud, Fathul (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2025)
Supervision in Islam plays an important role in maintaining morality and justice in social life, especially in the context of ethics and leadership. This study aims to identify, analyze, and synthesize the principles of supervision in the Qur'an and Hadith and examine their implications for ethics and leadership in Muslim society. The method used is a Systematic Literature Review, with literature sources drawn from indexed databases such as Google Scholar, DOAJ, and Scopus, limited to publications within the past ten years. The research findings indicate that the concepts of Hisbah, ethics, and accountability in Islamic leadership play a significant role in establishing a social order grounded in moral values and justice. Hisbah not only functions as a tool for social oversight but also as a mechanism for moral education, instilling ethical awareness in individuals and communities. This principle contributes to enhancing transparency, accountability, and social welfare, particularly within government and Islamic institutions. The main findings indicate that Islamic oversight systematically shapes responsible leadership, prioritizes maqashid syariah, and encourages active community participation in collective moral oversight. However, the main challenge in its implementation is how Islamic oversight principles can be adapted to modern legal systems without disregarding human rights. Therefore, a flexible and contextual approach is needed to ensure that Islamic oversight principles remain relevant and can be effectively applied in various aspects of community life.